Education and Prevention of Posture Disorders in Elementary School Students in Pinrang Regency - Ibnu, Indra Fajarwati; Syarifuddin, Fadillah (Journal of Mestika Nusantara Satu Community Services, 2025)
Changes in posture that occur during childhood result from incorrect sitting habits, non-ergonomic standing positions, improper backpack use, and the dangers of playing pull-the-chair games, which can cause fracture injuries. If these habits are not corrected early, they will persist into adulthood, potentially causing musculoskeletal system disorders. Early posture education is an effective solution to prevent posture disorders and abnormalities. Objective: This activity aims to provide education and prevention of posture disorders to 5th grade students at SDN 26 Pinrang, SDN 171 Pinrang, and SDN 251 Pinrang in Desa Mamminasae, Kecamatan Paleteang, Pinrang Regency. Methods: Education was delivered using PowerPoint presentations and live demonstrations. Results: The evaluation showed an increase in 5th grade students' knowledge regarding correct sitting and standing positions, proper backpack use, and the dangers of playing pull-the-chair games. Conclusion: Through early counseling and education on posture disorders, students and school staff understood the importance of maintaining proper posture to prevent musculoskeletal disorders.